Analysis of Efficiency Level of SRB West Java Region for the period of 2018-2020 - Lu’lu Dzahidah; Firmansyah Firmansyah; Nining Nurhasanah; Aziz Budi Setiawan (Jurnal Ekonomi dan Perbankan Syariah, 2022)
This study aims to measure the efficiency level of Islamic Rural Bank (BPRS) using the Data Envelopment Analysis (DEA) method. The research is a quantitative study using secondary data. The population in this study are all BPRS in the West Java region registered with the financial services Authority as of December 2018 as many as 27. And the sample used in this study was 12. This study used an intermediation approach with orientation input and using BBC/VRS measurements. The result of this study is 1 BPRS that achieve perfect efficiency levels achieve perfect efficiency levels in constant positions base on Score (SE).